Activation of TRIF-dependent and independent immune responses by neisserial heat shock protein complex vaccines. Issue 11 (1st November 2016) - Ng, Garrett Z.; Han, Jia-Xi; Colaco, Camilo A.; Sutton, Philip
ASBTRACT: Heat shock protein Complex (HspC) vaccines are composed of Hsp purified from pathogenic bacteria along with their chaperoned protein cargo. Mouse studies have shown that HspC vaccines can induce a strong immune response against pathogenic bacteria without addition of an exogenous adjuvant. These vaccines are now entering clinical trials. It was predicted, but not previously tested, that HspC vaccines induce an immune response due to the activation of Toll-Like Receptors (TLR) by their component Hsp. Recently we tested this supposition and found that while this held true for the cellular response to neisserial HspC vaccines, strong antigen-specific antibody responses were surprisingly generated in mice deficient in MyD88 and thus most TLR signaling. This suggested an unidentified mechanism by which HspC vaccines induce an antibody response. We have now examined the antigenic profile of this response and found no evidence that this is due to the induction of T-independent antibodies. Examination of the MyD88-dependent signaling pathways involved in the cellular response to neisserial HspC showed that both TRIF-dependent and TRIF-independent pathways are activated, each resulting in the secretion of different cytokines. Hence the mechanism of action of HspC vaccines is clearly more complicated than originally thought.